Effects of omnivorous and vegetarian diets in neuromuscular adaptations to physical exercise: A systematic review - Seimetz, L. G.; Zanella, P. B. (Science & Sports, 2024)
Purpose The aim of this systematic review is to analyze the scientific evidence in relation to neuromuscular adaptations to physical exercise in vegetarians versus omnivores.